#### Answer

$3x^2-6x$

#### Work Step by Step

$y=x^3-3(x^2+\pi^2)=x^3-3x^2-3\pi^2$
$y'=3x^2-2\times3x-0=3x^2-6x$

Published by
Pearson

ISBN 10:
0321999584

ISBN 13:
978-0-32199-958-0

$3x^2-6x$

$y=x^3-3(x^2+\pi^2)=x^3-3x^2-3\pi^2$
$y'=3x^2-2\times3x-0=3x^2-6x$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.